Numerical investigation of GFRP bars contribution on performance of concrete structural elements - Pegah Aghabozorgi; Alireza Khaloo; Sina Hassanpour (Numerical Methods in Civil Engineering)
In this study, twenty glass fiber reinforced polymer (GFRP) reinforced concrete specimens were modelled using finite element method to predict the effect of GFRP compressive bars on the flexural strength and ductility of GFRP reinforced concrete beams. Also, the contribution of GFRP longitudinal rebars to the load-carrying capacity of reinforced concrete columns is determined. The concrete elastoplastic behaviour after the peak load was defined using the concrete damaged plasticity model in ABAQUS software. The FE results were validated using the experimental data reported in the literature. The results demonstrated a close agreement between the load-displacement curves obtained from numerical analysis and the tests. An increase in the percentage of GFRP compressive reinforcement resulted in slightly higher energy absorption and ductility in the GFRP concrete beams. According to the FE analysis, increasing GFRP compressive reinforcement has a minor influence on the flexural strength of beams. Moreover, decreasing the percentage of longitudinal reinforcement leads to a reduction in the strength and ductility of columns, and higher loss in strength was observed when greater eccentricity was applied in columns.